Development of a New Test Method To Evaluate Dynamic Stability of Self-Consolidating Concrete - Alami, Mohammad Musa; Erdem, Tahir Kemal; Erdem, Tahir Kemal; Khayat, Kamal H. (RILEM Publications SARL, 2016)
Although many different test methods have been proposed to evaluate the static stability of self-consolidating concrete (SCC), limited test methods have been developed to determine dynamic segregation of SCC. In this study, a new apparatus was developed for testing the dynamic stability of SCC. The new method was called as "Dynamic Sieve Segregation Test" (DSST) which provides a numerical result referred to the "dynamic segregation ratio" (DSR). Higher DSR values indicate dynamically less stable mixtures. Several correlations were successfully established between the test results. SCC mixtures with higher slump flow, higher coarse aggregate-to-total aggregate ratio or higher maximum aggregate size (Dmax) resulted in higher DSR values. A maximum DSR value of 30% was proposed for a dynamically stable SCC. The repeatability of DSST was found to be high with a COV value of 5.30%. Based on the results, DSST was found to be a suitable method to evaluate the dynamic stability of SCC.
8th International RILEM Symposium on Self-Compacting Concrete -- MAY 15-18, 2016 -- Washington, DC
Keywords: Dynamic stability; New test method; Stability; SCC